INFLUENCE OF BRAND IMAGE ON BUYING DECISION (STUDY AULIA WEDDING GALLERY) - Zarfa Nuary, Fadhila; Bursan, Rinaldi; Siti Ambarwati, Dwi Asri (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
The development of the decoration, make-up and fashion business is getting faster and tighter because all of them appear and try to bring fresh things to offer to consumers. This creates an increasingly competitive arena of competition in this business field. This study aims to determine how much influence the company's brand image has on consumer decisions to make a purchase, with the subject of as many as 102 consumers who have used the services of Aulia Wedding Gallery Lampung aged 17 years and over. The method used in this research is a questionnaire, interviews and direct observation in the field, with data testing techniques in the form of validation tests, reliability tests, T-tests, and F tests. significant on the Purchase Decision, where all data have met the requirements of validity and reliability with the results of the T test and F test of 0 < 0.05 which indicates that accept Ha and reject H0. Then the data is also strengthened by consumer answers who strongly agree and agree for the product image indicator of 98.04%, the producer image indicator and product excellence of 97.06%, the user image indicator of 96.57%, the indicator recommending to others 95 ,1%, the repurchase indicator is 97.06%, and the maturity indicator for a product is 98.04%.